Análisis de peligrosidad a deslizamientos en la parroquia San Pedro de la Bendita, cantón Catamayo, provincia de Loja - Sarango Torres, Félix David (2022)
San Pedro de la Bendita parish is located in the Province of Loja, Canton Catamayo, to 53 km from the city of Loja and at 1800 meters above sea level, it has an area of 146,67 km2, geographically limiting the parishes of El Cisne and Zambi to the North, to the South with Nambacola parish, to the East with the cantonal head of Catamayo and to the West with the Zambi and Catacocha parishes. The purpose of this work was to identify and characterize the areas with the greatest risk of landslides through multicriteria evaluation, putting into practice the Hierarchical Analysis Process (AHP) developed by Thomas Saaty in 1980, which uses a series of variables and criteria arranged in a matrix ranked and weighted based on the importance and incidence of each of these. The variables used in this research were of two types: conditioning variables (geomorphology, lithology, slopes and land use) and trigger variables (rainfall intensity) which were analyzed with a probability of occurrence of 1% in a return period of 100 years As a final result of the hazard analysis, it is found that in the study area there is a percentage of 69,66 % of high hazard, followed by 22,57 % with medium hazard, 4,68 % with very low hazard and 3,09 % low hazard of landslides. The methodology used presents an 86,36 % efficiency, determined based on the inventory of landslides carried out and the corroboration with the defined danger zones. Keywords: Hierarchical Analysis Process, multicriteria evaluation, hazard, landslide inventory, determining factors, trigger.